Volt-Var Optimization with Power Management of Plug-in Electric Vehicles for Conservation Voltage Reduction in Distribution Systems - Quijano, Darwin A. [UNESP] (2022)
This paper addresses the problem of Volt-Var optimization for conservation voltage reduction (CVR) implementation in medium voltage electric distribution systems (EDS) with high penetration levels of renewable energy sources (RES)-based distributed generation (DG). The proposed strategy seeks to coordinate the power dispatch of aggregated electric vehicles (EVs) for EDS voltage control taking into account technical characteristics and the driving patterns of individual EVs. The strategy is for the day-ahead operation scheduling, where decisions are made based on predictions of RES-based DG power production, conventional load consumption and EV driving patterns. Forecast errors are taken into account through a two-stage stochastic programming formulation, where probability density functions are used to describe the uncertainties of predicted parameters. Simulations were carried out on a 33-bus test system and results showed energy savings of up to 3% when EVs participate in voltage control.